Integration of agricultural cooperatives into the management process of the economy plan in Cuba (Gestión y Gerencia, 2023)
Cooperativism is an interesting option for those farmers with difficulties to carry out their production since, by associating, they increase the efficiency of their businesses, at the same time that it opens the doors to soft credits, technical-financial support and they have the possibility of acquiring assets at a lower price. cost, among other benefits. In updating the budding Cuban economic model, the cooperatives are called upon to join the National Economy Plan (PEN). The present investigation fits into this guideline, specifically postulates a rational procedure to integrate cooperatives into the PEN. The methodology used is of the qualitative and quantitative type, where it was necessary to systematize the theoretical and methodological foundations associated with the economic planning process of cooperative companies, to later validate the result through expert criteria by the Delphi method and verify its reliability by Alpha. de Cronbach. Where the expected results are aimed at improving the coordination and integration of productive, economic and financial aspects, in order to enhance their initiatives and efforts to achieve economic objectives, with maximum efficiency and the collaboration of their associates. To avoid distortions in the results, contributing to better planning and organization of cooperative companies, by calculating efficiency indicators.
Keywords: Agricultural cooperatives; indicators; economic planning; procedure